A dual‐AAV approach restores fast exocytosis and partially rescues auditory function in deaf otoferlin knock‐out mice - Hanan Al‐Moyed; Andreia P Cepeda; SangYong Jung; Tobias Moser; Sebastian Kügler; Ellen Reisinger (EMBO Molecular Medicine, 2018)
Abstract Normal hearing and synaptic transmission at afferent auditory inner hair cell (IHC) synapses require otoferlin. Deafness DFNB9, caused by mutations in the OTOF gene encoding otoferlin, might be treated by transferring wild‐type otoferlin cDNA into IHCs, which is difficult due to the large size of this transgene. In this study, we generated two adeno‐associated viruses (AAVs), each containing half of the otoferlin cDNA. Co‐injecting these dual‐AAV2/6 half‐vectors into the cochleae of 6‐ to 7‐day‐old otoferlin knock‐out (Otof−/−) mice led to the expression of full‐length otoferlin in up to 50% of IHCs. In the cochlea, otoferlin was selectively expressed in auditory hair cells. Dual‐AAV transduction of Otof−/− IHCs fully restored fast exocytosis, while otoferlin‐dependent vesicle replenishment reached 35–50% of wild‐type levels. The loss of 40% of synaptic ribbons in these IHCs could not be prevented, indicating a role of otoferlin in early synapse maturation. Acoustic clicks evoked auditory brainstem responses with thresholds of 40–60 dB. Therefore, we propose that gene delivery mediated by dual‐AAV vectors might be suitable to treat deafness forms caused by mutations in large genes such as OTOF.